2005
DOI: 10.1103/physrevb.71.014305
|View full text |Cite
|
Sign up to set email alerts
|

Berry phase and entanglement in the icosahedralH(g2h)Jahn-Teller system with trigonal minima

Abstract: The H ͑g 2h͒ Jahn-Teller problem in the trigonal regime offers an example of a dynamic ground-state crossover from a degenerate to a singlet state. This crossover is connected to a change in tunneling paths which results in a loss of Berry phase. Previous studies tried to explain the entanglement which lies at the basis of this phenomenon using two-dimensional ͑2D͒ cuts through coordinate space but have reached opposite interpretations. In this paper we introduce a method which scans the topology of the full c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In this case too, only two adiabaticsheets of the fivefold manifold are predicted to manifest GP: case(2,3). Such a result seem at first to contradict existing evidence on the nature of the dynamic ground state adiabatic PES, which has been examined in detail[47,139,140].In fact, the JT effect of the icosahedral quintuplet term in the trigonal regime shows an intriguing crossover of dynamic states from a degenerate to a singlet state, with coupling strength showing an apparent correlation with the phase of the tunneling paths through such minima. At stronger coupling the dominant tunneling process is believed to consist of closed loops spanning cycles of five wells, with a vanishing GP associated with these loops.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…In this case too, only two adiabaticsheets of the fivefold manifold are predicted to manifest GP: case(2,3). Such a result seem at first to contradict existing evidence on the nature of the dynamic ground state adiabatic PES, which has been examined in detail[47,139,140].In fact, the JT effect of the icosahedral quintuplet term in the trigonal regime shows an intriguing crossover of dynamic states from a degenerate to a singlet state, with coupling strength showing an apparent correlation with the phase of the tunneling paths through such minima. At stronger coupling the dominant tunneling process is believed to consist of closed loops spanning cycles of five wells, with a vanishing GP associated with these loops.…”
mentioning
confidence: 79%
“…Belonging to the symmetry group [11] SO (5) In line with the other JT problems, use will then be made of the rotation matrix [47], who have scanned the topology of the full coordinate space using a net of triangular cross sections between the ten D 3d minima. By expressing the GP of every loop on the PES in terms of such 2D triangular cross sections, they have found [47] that the absence of GP for the cycles containing five trigonal wells originates from two seams of conical intersections going through these cycles. Suffice it to note that the absence of GP effect on the adiabatic ground state PES does not invalidate our prediction that only two sheets of the fivefold electronic manifold manifest GP.…”
Section: High Electronic Orbital Degeneraciesmentioning
confidence: 99%
See 1 more Smart Citation
“…The JT effects in these systems are interesting because the icosahedral symmetry results in high electronic and vibrational degeneracies, 4 with additional complications arising due to the nonsimple reducibility of the H representation. 5,6 In this paper, we will concentrate on JT effects in the C 60 2+ cation, in which coupling between the two holes of H u symmetry to eight vibrational modes of h g symmetry is taken into account. The holes also couple to two a g modes and six g g modes, but it has been shown that these modes do not result in any significant distortions 7 so they will not be considered here.…”
Section: Introductionmentioning
confidence: 99%
“…Vibronic ground-state degeneracy (VGSD) in JT models appears frequently when linear vibronic couplings dominate [10,11] (for a recent proposal of direct noninterferometric experimental verification of VGSD, see e.g., [15,16]), although there are exceptions [17][18][19][20]. More specifically, there exists a particular class of JT models for which VGSD is guaranteed to exist whenever the adiabatic approximation (Born-Oppenheimer [21] with inclusion of Berry phase effects [22,23]) is valid [10,11,24].…”
mentioning
confidence: 99%